Chili pepper extends lifespan in a concentration-dependent manner and confers cold resistance on Drosophila melanogaster cohorts by influencing specific metabolic pathways. Issue 15 (17th July 2022) - Semaniuk, Uliana V.; Gospodaryov, Dmytro V.; Strilbytska, Olha M.; Kucharska, Alicja Z.; Sokół-Łętowska, Anna; Burdyliuk, Nadia I.; Storey, Kenneth B.; Bayliak, Maria M.; Lushchak, Oleh
Abstract : Chili powder in concentrations of 0.04–0.12% extended median lifespan in fruit flies by 9–13%. The metabolic changes in chili-fed flies was depended on gender. Chili-fed individuals had higher resistance to stress induced by cold. Abstract : Chili powder is a widely used spice with pungent taste, often consumed on a daily basis in several countries. Recent prospective cohort studies showed that the regular use of chili pepper improves healthspan in humans. Indeed, chili pepper fruits contain phenolic substances which are structurally similar to those that show anti-aging properties. The objective of our study was to test whether consumption of chili-supplemented food by the fruit fly, Drosophila melanogaster, would prolong lifespan and in which way this chili-supplemented food affects animal metabolism. Chili powder added to food in concentrations of 0.04%–0.12% significantly extended median lifespan in fruit fly cohorts of both genders by 9% to 13%. However, food supplemented with 3% chili powder shortened lifespan of male cohorts by 9%. Lifespan extension was accompanied by a decrease in age-independent mortality ( i.e., death in early ages). The metabolic changes caused by consumption of chili-supplemented food had a pronounced dependence on gender. A characteristic of both fruit fly sexes that ate chili-supplemented food was an increased resistance to cold shock. Flies of both sexes had lower levels of hemolymph glucose when they ate food supplemented with low concentrations of chili powder, as compared with controls. However, males fed on food with 3% chili had lower levels of storage lipids and pyruvate reducing activity of lactate dehydrogenase compared with controls. Females fed on this food showed lower activities of hexokinase and pyruvate kinase, as well as lower ADP/O ratios, compared with control flies.